Psychological beliefs and financial well-being among working adults: the mediating role of financial behaviour. Issue 2 (21st October 2021) - She, Long; Rasiah, Ratneswary; Turner, Jason James; Guptan, Vinitha; Sharif Nia, Hamid
Abstract : Purpose: This study aimed to assess the impact of psychological beliefs (subjective financial knowledge, financial attitude and locus of control) on financial well-being, as well as the mediating role of financial behaviour in the relationship between psychological beliefs and financial well-being among working adults in Malaysia. Design/methodology/approach: A survey-based questionnaire was used to elicit information from a total of 500 working adults from Malaysia. Partial least squares structural equation modelling (PLS-SEM) was used to assess the measurement model and the proposed mediation model. Findings: The results showed that subjective financial knowledge, financial attitude and locus of control have a positive impact on both financial behaviour and financial well-being. The results also showed that financial behaviour mediates the relationships between financial attitude and financial well-being, as well as between locus of control and financial well-being. Originality/value: Given the anticipated global economic recession, a better understanding of how individuals manage their finances becomes ever more crucial. The findings from this research inform policymakers, practitioners and academics on the importance of psychological factors and financial management practices on financial well-being, addressing an identified gap in the current literature.